The Role of ICARDA’s Germplasm Health Unit (GHU) in Improving Plant Health and Safeguarding the Biodiversity of Legume and Cereal Crops - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam; Darwish, Iman (Arab Society of Plant Protection (ASPP), 2023)
In order to safeguard countries from quarantine risks (insect pests, pathogens, nematodes, parasitic weeds) associated with the movement of legume (faba bean, lentil, chickpea, grasspea) and cereal (wheat and barley) germplasm, ICARDA’s Germplasm Health Unit (GHU) follows a regulatory and quarantine program implemented in close collaboration with competent institutions where ICARDA has platforms for crop breeding, germplasm multiplication and evaluation and genetic resources exchange. GHU serves as ICARDA’s gateway for legume and cereal germplasms exchange by ensuring compliance with the FAO International Plant Protection Convention (IPPC) procedures and the International Standards for Phytosanitary Measures (ISPMs) applied by National Plant Protection Organizations (NPPOs) to prevent the introduction and control the spread of pests along with plants or plant products. ICARDA’s GHU is involved in the following responsibilities: (1) Develop and validate diagnostic tools and procedures for germplasm health testing and share the updated technology with the NPPOs; (2) Create and adopt phytosanitary procedures to generate pest-free germplasm and avert the spread of quarantine pests in legume and cereal germplasm transfers; (3) Ensure that all movement of legume and cereal germplasms comply with guidelines of importing and exporting countries to avoid any breaches of the host and receiving countries’ quarantine protocols; (4) Conduct pest risk assessment of germplasm activities, including conservation, seed increase and transfers; (5) Organize GHU community of practice to form a network of centers for transboundary pest prevention; (6) Contribute to the phytosanitary capacity development.